PREOPERATIVE RISK FACTORS FOR ACUTE KIDNEY INJURY AFTER LIVER TRANSPLANTATION: RESULTS FROM A CROSS-SECTIONAL STUDY IN NORTHEAST OF BRAZIL - GOMES JUNIOR,Raimundo Martins (2018)
ABSTRACT BACKGROUND: Acute kidney injury (AKI) is a common complication in the immediate postoperative period of patients undergoing liver transplantation. OBJECTIVE: The aim of this study was to evaluate preoperative risk factors for AKI after liver transplantation. METHODS: A cross-sectional study was conducted with adults submitted to orthotopic liver transplantation at a reference hospital in Fortaleza, Northeast of Brazil, from January to December 2016. Preoperative risk factors were evaluated for AKI development in the immediate postoperative period. AKI was defined according to the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. RESULTS: A total of 40 patients were included in the study. AKI was found in 85% of patients in the first 24 hours after transplantation, most of them (40%) classified in KDIGO stage 1. Preoperative data indicate that serum albumin levels were lower in the KDIGO stage 3 group compared to the non-AKI group, as well as the hematocrit levels. Direct bilirubin (DB) was higher in the KDIGO stage 3 group compared to the group without AKI, as well as alkaline phosphatase (AP) and gamma-glutamiltransferase (GGT). In a logistic regression analysis independent risk factors for AKI were increase levels of AP, GGT and DB and decrease level of serum albumin. CONCLUSION: Low levels of serum albumin, and elevated levels of DB, AP and GGT in the preoperative period are risk factors for AKI development after liver transplantation.